A method for three-dimensional stem analysis and its application in a study on the occurrence of resin pockets in Pinus patula - Lerm, Frederik Johannes (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFor)--Stellenbosch University, 2013.